2007
DOI: 10.1002/tea.20122
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' and prospective teachers' explanations of liquid‐state phenomena: A comparative study involving three European countries

Abstract: As contact with liquids occurs from an early stage in individuals' lives, children construct explanations for liquids and liquid‐state phenomena. These may differ from the accepted scientific explanations, interfere with formal teaching, and even persist until entry into higher education. The objective of this investigation is to compare student‐teachers' and in‐service science teachers' explanations for liquid‐state phenomena, in three European countries. Data were collected by means of a questionnaire applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
1
21
0
1
Order By: Relevance
“…There are many studies suggesting that culture has no obvious effect on misconceptions about different topics of physics (Leite, Mendoza & Borsese, 2007). The research studies cited here and many others suggest that students and teachers in different cultures have similar kinds of difficulties in their understanding of the concepts of force and motion, and hold similar misconceptions.…”
Section: Results and Implicationsmentioning
confidence: 62%
“…There are many studies suggesting that culture has no obvious effect on misconceptions about different topics of physics (Leite, Mendoza & Borsese, 2007). The research studies cited here and many others suggest that students and teachers in different cultures have similar kinds of difficulties in their understanding of the concepts of force and motion, and hold similar misconceptions.…”
Section: Results and Implicationsmentioning
confidence: 62%
“…Many researchers ascribes teaching experience as the primary source of PCK development (Van Driel, De Jong, & Verloop, 2002;Van Driel, Verloop, & De Vos, 1998;Grossman, 1990;Magnusson et al, 1999;Van Driel, Beijaard, & Verloop, 2001), while others emphasizes that teaching experience alone does not lead necessarily to robust PCK (Leite, Mendoza, & Borsese, 2005;Friedrichsen et al, 2009). For instance, Lee, Brown, Luft and Roehring (2007) support that PCK can be improved through teaching experience; therefore preservice and novice teachers may possess limited or minimal PCK.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…However, a review of the extant literature relative to the development of teachers' science SMK through teaching experience provides conflicting results. On one hand, studies have shown that teachers do learn science content through teaching experience (Arzi & White, ; Donna & Hick, ; Grossman, Wilson, & Shulman, ; Leite, Mendoza, & Borsese, ; Nixon et al, ; Smith, ; Strimaitis, Southerland, Kraft, & Schultz, ). Evidence for these findings is drawn from a variety of sources, including self‐report data (e.g., Donna & Hick, ), cross‐sectional studies (e.g., Nixon et al, ), long‐term longitudinal studies (e.g., Arzi & White, ), and shorter term studies (e.g., Smith, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interestingly, the majority of existing studies have focused on secondary (Arzi & White, ; Leite et al, ; Nixon et al, ) or tertiary teachers (Strimaitis et al, ). Thus, it remains unclear whether these same results may be true of elementary teachers, whose SMK preparation differs dramatically from that of secondary and tertiary teachers who focus exclusively on science.…”
Section: Literature Reviewmentioning
confidence: 99%